2017
DOI: 10.1186/s40168-017-0282-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal inheritance of bifidobacterial communities and bifidophages in infants through vertical transmission

Abstract: BackgroundThe correct establishment of the human gut microbiota represents a crucial development that commences at birth. Different hypotheses propose that the infant gut microbiota is derived from, among other sources, the mother’s fecal/vaginal microbiota and human milk.ResultsThe composition of bifidobacterial communities of 25 mother-infant pairs was investigated based on an internal transcribed spacer (ITS) approach, combined with cultivation-mediated and genomic analyses. We identified bifidobacterial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
241
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 259 publications
(257 citation statements)
references
References 64 publications
(80 reference statements)
13
241
1
2
Order By: Relevance
“…Current studies indicate that bifidobacteria are transmitted vertically from the mother's vagina, GI tract, or breast milk. This is supported by findings by Duranti et al [22], who used a novel internal transcribed spacer (ITS) approach trialled previously [23]. Duranti et al found genomically identical bifidobacteria strains in faecal and milk samples from 24 mother-infant pairs.…”
Section: Bifidobacterium Across the Life Coursesupporting
confidence: 70%
See 1 more Smart Citation
“…Current studies indicate that bifidobacteria are transmitted vertically from the mother's vagina, GI tract, or breast milk. This is supported by findings by Duranti et al [22], who used a novel internal transcribed spacer (ITS) approach trialled previously [23]. Duranti et al found genomically identical bifidobacteria strains in faecal and milk samples from 24 mother-infant pairs.…”
Section: Bifidobacterium Across the Life Coursesupporting
confidence: 70%
“…These findings provide initial insights as to why vaginal delivery provides a higher abundance of Bifidobacterium in infants, over a caesarean section (C-section) delivery [24,25]. Following birth, breast milk may provide a secondary delivery route for further bifidobacteria [22,26] and additionally drives proliferation of bifidobacteria due to its unique nutritional milieu of human milk oligosaccharides (HMOs), proteins, and lipids [27][28][29]. Notably, a reduced abundance of Bifidobacterium in infants is highly correlated to chronic diseases, including asthma and obesity [30].…”
Section: Bifidobacterium Across the Life Coursementioning
confidence: 99%
“…For most animals, their microbial community is established over development through interactions with the environment, through diet, as well as interactions with other organisms (Abdul Rahman et al, ; Blaser & Dominguez‐Bello, ; Carrasco et al, ; da Costa & Poulsen, ; Estes et al, ; Funkhouser & Bordenstein, ; Gilbert, ; Korpela et al, ; Kostic et al, ; Morse et al, ; Mueller, Bakacs, Combellick, Grigoryan, & Dominguez‐Bello, ; Perez‐Muñoz, Arrieta, Ramer‐Tait, & Walter, ; Schwab, Riggs, Newton, & Moczek, ; Shukla, Vogel, Heckel, Vilcinskas, & Kaltenpoth, ; Torrazza & Neu, ; Wang & Rozen, ). Of interest is the role that parent–offspring interactions play in the microbial acquisition during early development, specifically from mother to her offspring (Adair & Douglas, ; Dimmitt et al, ; Duranti et al, ; Fox & Eichelberger, ; Funkhouser & Bordenstein, ; Gilbert, ; Jašarević, Rodgers, et al, ; Korpela et al, ; Kostic et al, ; Perez‐Muñoz et al, ; Schwab et al, ; Torrazza & Neu, ; Wade, ; Walker, Clemente, Peter, & Loos, ).…”
Section: Introductionmentioning
confidence: 99%
“…This forces vertical symbiont transmission to occur through incorporation during oogenesis or by inoculating the external egg surface for consumption immediately upon juvenile emergence (Abdul Rahman et al, ; Estes et al, ; Funkhouser & Bordenstein, ; Schwab et al, ; Shukla et al, ). Viviparous (live‐bearing) animals can have extensive and complex interactions between mother and offspring during gestation and birth, the impacts of which can last for a few days to years (Cao‐Lei et al, , ; Duranti et al, ; Funkhouser & Bordenstein, ; Jašarević, Rodgers, et al, ; Jiménez‐Chillarón et al, ; Ma et al, ; Ogawa & Miura, ; Poulin & Thomas, ; Stein & Lumey, ; Torrazza & Neu, ; Weiss et al, ). These prolonged interactions provide means for multiple routes of vertical transmission of microbes from mother to her progeny (Funkhouser & Bordenstein, ; Ma et al, ; Mueller et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation